Luteinizing hormone, testosterone and inhibin B levels in the peripubertal period and racial/ethnic differences among boys aged 6–11 years: analyses from NHANES III, 1988–1994 - Lee, Peter A. (2010)
OBJECTIVE: To determine whether the initial physical findings of puberty are accompanied by hormonal evidence of pubertal activation of the hypothalamic–pituitary–gonadal (HPG) axis and whether racial/ethnic differences exist, we have analysed hormone levels in relation to age, onset of puberty and race/ethnicity. DESIGN: Cross-sectional analysis of luteinizing hormone (LH), testosterone (T) and inhibin B from banked sera from a representative sample of US boys aged 6·0–11·99 years who participated in the National Health and Nutrition Examination Survey (NHANES) III. PATIENTS: Eight hundred and twenty-eight boys having sera including 228 non-Hispanic white (NHW), 266 non-Hispanic black (NHB), 288 Mexican-American (MA) and 46 ‘other’. MEASUREMENTS: Using analysis of variance and linear regression techniques, concentrations of LH, T and inhibin B were compared by race/ethnicity for all boys and pubertal status (Tanner's Staging 1, 2 and 3+) for boys aged 8 years and older. Receiver operating curves were utilized to identify cut-points predictive of pubertal HPG status. RESULTS: Mean hormones levels progressively increased with age. Receiver operating characteristic (ROC) curves indicate hormones are consistent with pubertal onset as indicated by Tanner stage 2, except for T and genital stage 2. Inhibin B and LH levels increased significantly by genital stage after adjusting for age and race/ethnicity, while LH and T concentrations increased significantly across pubic hair stages. Levels of inhibin B were significantly higher for NHB boys compared with other racial/ethnic groups. CONCLUSIONS: In these cross-sectional findings, hormone levels rise gradually as boys approach the peripubertal age, whereas an abrupt rise was not associated with the onset of physical changes of puberty.